Fin whales of the Great Bear Rainforest : Balaenoptera physalus velifera in a Canadian Pacific fjord system - Keen, Eric M.; Pilkington, James; O'Mahony, Eadin; Thompson, Kim-Ly; Hendricks, Benjamin; Robinson, Nicole; Dundas, Archie; Nichol, Linda; Alidina, Hussein M.; Meuter, Hermann; Picard, Chris R.; Wray, Janie (PLOS ONE, 2023)
Funding: This research was supported by a Mitacs Accelerate Internship (IT21479); the Save Our Seas Foundation; Willow Grove Foundation; Donner Canadian Foundation; Tides Canada; LUSH Charity Pot; private donations to North Coast Cetacean Society; Fisheries and Oceans Canada; and the Canada Nature Fund for Aquatic Species at Risk (CANAFSAR 2019-2021). Fin whales (Balaenoptera physalus) are widely considered an offshore and oceanic species, but certain populations also use coastal areas and semi-enclosed seas. Based upon fifteen years of study, we report that Canadian Pacific fin whales (B. p. velifera) have returned to the Kitimat Fjord System (KFS) in the Great Bear Rainforest, and have established a seasonally resident population in its intracoastal waters. This is the only fjord system along this coast or elsewhere in which fin whales are known to occur regularly with strong site fidelity. The KFS was also the only Canadian Pacific fjord system in which fin whales were commonly found and killed during commercial whaling, pointing to its long-term importance. Traditional knowledge, whaling records, and citizen science databases suggest that fin whales were extirpated from this area prior to their return in 2005-2006. Visual surveys and mark-recapture analysis documented their repopulation of the area, with 100-120 whales using the fjord system in recent years, as well as the establishment of a seasonally resident population with annual return rates higher than 70%. Line transect surveys identified the central and outer channels of the KFS as the primary fin whale habitat, with the greatest densities occurring in Squally Channel and Caamano Sound. Fin whales were observed in the KFS in most months of the year. Vessel- and shore-based surveys (27,311 km and 6,572 hours of effort, respectively) indicated regular fin whale presence (2,542 detections), including mother-calf pairs, from June to October and peak abundance in late August-early September. Seasonal patterns were variable year-to-year, and several ...